THE PRACTICE OF THE INTERNATIONAL CRIMINAL COURT IN PROVING WAR CRIMES: IMPLICATIONS FOR UKRAINE - Beryslavska, Oksana; Havryshkevych, Ihor (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . The article examines the significance of the Chamber trial Manual for improving law enforcement practice in Ukraine, which serves as an important source for understanding the procedural aspects of evidence collection and proof, as well as the trial of cases involving the most serious international crimes. The author highlights the expediency of applying the practice of the International Criminal Court (hereinafter – ICC) in Ukrainian criminal proceedings concerning war crimes. The author takes into account the recommendations of the ICC judges regarding the study of the interpretation of concepts based on verdicts in similar proceedings (in particular, cases concerning war crimes, aggression, sexual and genderbased violence, etc.) M e t h o d s . The main research method is the comparative legal method, which is applied to the Chamber trial Manual and the Resolutions of the Supreme Court Plenums (hereinafter – SC) in order to compare the status of these documents, the mandatory nature of their implementation, and the adaptation of the ICC procedures to the investigation of war crimes in Ukraine. In addition, the author applied the historical and legal method, which consists in analyzing legislation, identifying patterns and trends in the institutionalization of judicial precedents, and studying the activities of international tribunals and the ICC in a historical context. R e s u l t s . The author identifies a number of gaps in the criminal law field, particularly regarding the absence of an official translation of the Chamber trial Manual and ICC case law. In view of this, it is proposed to supplement the Criminal Procedural Code of Ukraine (hereinafter – CPC), specifically Section IX-2 ‘Peculiarities of Cooperation with the International Criminal Court’, with a provision obliging the central authorities of Ukraine to apply the practice of the International Criminal Court, along with the resolutions of the Supreme Court Plenum. C o n c l u s i o n s . A comparison of the Chamber trial Manual with the SC Plenary Resolutions under status theory demonstrates that they share a common goal – the unification of law enforcement practice - but in different legal contexts. The Manual is an internal document of the ICC aimed at regulating procedures in cases of international crimes, while the SC Plenum Resolutions have a broader impact within the national legal system of Ukraine. Neither document has direct legislative force, but both play a key role in ensuring consistency and fairness in the administration of justice. Given that the Ministry of Justice of Ukraine is entrusted with the task of translating ICC documents in accordance with Article 618(4)(3) of the Criminal Procedural Code of Ukraine, it is necessary to organize the translation of the Chamber trial Manual and ensure the integration of the case law it contains into Ukraine’s system of criminal procedure law.